Association of ABO Blood Group with Delayed Cerebral Ischemia and Clinical Outcomes Following Aneurysmal Subarachnoid Hemorrhage in Pakistan - Azeem, Saleha; Ashraf, Mohammad; Kamboh, Usman Ahmad; Raza, Muhammad Asif; Farooq, Minaam; Cheema, Huzaifa Ahmad; Tariq, Simra; Choudhary, Nabeel; Hussain, Syed Shahzad; Ashraf, Naveed (Asian Journal of Neurosurgery, 2023)
Background The ABO blood type, due to its various hemostaseologic properties, has been associated with several vascular diseases, including aneurysmal subarachnoid hemorrhage (aSAH). However, the role of ABO blood type in delayed cerebral ischemia (DCI) onset and other clinical outcomes after aSAH is largely unexplored. This study aimed to investigate the association between ABO blood type and outcomes after aSAH, primarily DCI.Methods A retrospective analysis was made on the data collected from 175 aSAH patients at a tertiary supraregional neurosurgery department over 5 years. Socio-demographic factors, clinical variables (DCI, mFG, WFNS grade, and Glasgow Outcome Scale at discharge), EVD placement, and aneurysm size were analyzed for their association with ABO blood type.Results DCI was reported in 25% of patients with ‘O’ blood type and 9.6% with ‘non-O’ blood type. A stepwise logistic regression model showed that after adjusting for BMI, mFG, WFNS grade, and EVD placement, ‘O’ type blood group was an independent risk factor for DCI, greatly increasing the risk of DCI as compared to ‘non-O’ type groups (OR = 3.27, 95% CI: 1.21–8.82).Conclusion This study provides evidence that individuals with ‘O’ blood type may have a higher risk of DCI onset after aSAH. However, further studies are essential to address the limitations of our work and confirm our findings.
Keywords: ABO blood group; subarachnoid hemorrhage; cerebral vasospasm; delayed cerebral ischemia; Pakistan